2016
DOI: 10.1186/s12862-015-0571-2
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus phylogeny and ecological differentiation of the “Eupelmus urozonus species group” (Hymenoptera, Eupelmidae) in the West-Palaearctic

Abstract: BackgroundThe ecological differentiation of insects with parasitic life-style is a complex process that may involve phylogenetic constraints as well as morphological and/or behavioural adaptations. In most cases, the relative importance of these driving forces remains unexplored. We investigate here this question for the “Eupelmus urozonus species group” which encompasses parasitoid wasps of potential interest in biological control. This was achieved using seven molecular markers, reliable records on 91 host s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 79 publications
1
19
1
Order By: Relevance
“…This demonstrates that selection alone cannot be responsible for the lack of growth differences observed between domesticated and wild salmon in rivers. Nevertheless, the largest size ratios observed here after the fish had been transferred to and reared in fish tanks (1:1.8), were lower than typically reported between domesticated and wild fish reared in that environment (typically 1:2–1:3, albeit with exceptions) 10 12 , 15 , 39 . Furthermore, the differences were much lower than observed in a study conducted in fish tanks (1:2.9) 11 that used part of the same genetic material as in the present study.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…This demonstrates that selection alone cannot be responsible for the lack of growth differences observed between domesticated and wild salmon in rivers. Nevertheless, the largest size ratios observed here after the fish had been transferred to and reared in fish tanks (1:1.8), were lower than typically reported between domesticated and wild fish reared in that environment (typically 1:2–1:3, albeit with exceptions) 10 12 , 15 , 39 . Furthermore, the differences were much lower than observed in a study conducted in fish tanks (1:2.9) 11 that used part of the same genetic material as in the present study.…”
Section: Discussioncontrasting
confidence: 71%
“…3 ), all of which demonstrate that fish of all genetic backgrounds managed the transition well. In addition, earlier studies have investigated whether domestication has led to adaptations to specific factors associated with farming conditions, such as; handling stress 11 , high rearing densities and social interactions 15 , 42 , feeding regimes 22 , and high-energy and pellet-based diets 39 . However, none of the above factors appear to inflate the relative growth differences between domesticated and wild salmon reared in fish tanks in farms.…”
Section: Discussionmentioning
confidence: 99%
“…All identifications were based on morphological characters. Eupelmus species were identified using the latest descriptions of the Eupelmus urozonus complex (Al Khatib et al 2014Khatib et al , 2016. Other species were identified by using an unpublished key to chalcidoid parasitoids in oak cynipid galls (Askew and Thuroczy, unpublished).…”
Section: Estimation Of D Kuriphilus Levels Of Infestationmentioning
confidence: 99%
“…Ecotypes that lack specialized adaptations to cope with H 2 S-related toxicity experience high mortality when migrating into sulfidic waters ( Tobler et al 2009 ; Plath et al 2013 ). On the other hand, sulfide-adapted fish have the ability to venture into surrounding non-sulfidic habitats at least for short periods of time, and both sulfide-adapted and not sulfide-adapted ecotypes can be found interacting in non-sulfidic water at the confluence of sulfidic creeks and (larger) non-sulfidic streams ( Sommer-Trembo et al 2016 ).…”
mentioning
confidence: 99%
“…Population genetic studies have identified low levels of gene-flow among P. mexicana populations from different habitat types but clearly detected evidence for unidirectional migration from sulfidic to non-sulfidic habitats ( Plath et al 2013 ). Even though female choice is thought to determine the outcome of male mate competition to a large extent as female poeciliids have a preferences for large, dominant males ( Sommer-Trembo et al 2016 ), and females (at least from non-sulfidic habitats) preferentially mate with males from their own population ( Tobler et al 2009 ; Plath et al 2010 , 2013 ; Greenway et al 2016 ), dominance hierarchies among males and use of coercive mating tactics ( Evans et al 2003 ; Plath et al 2007b ; Magurran 2011 ; Bierbach et al 2013 a) could, in theory, impede the evolution of reproductive isolation. At the interface between habitats where different ecotypes frequently meet, dominant males may monopolize females from different ecotypes and thus foster hybridization events ( Qvarnström et al 2012 ).…”
mentioning
confidence: 99%